PERBANDINGAN HASIL BELAJAR SISWA MENGGUNAKAN MEDIA GAMBAR DENGAN MEDIA AUDIO VISUAL PADA MATA PELAJARAN EKONOMI KELAS X SMA AL-WASHLIYAH 3 MEDAN - Nita Dahliani; Cita Ayni Putri Silalhi (Sekolah Tinggi Pariwisata Mataram, 2022)
This research is a quantitative research. The sampel in this study amounted to 18 people using the total sampling technique. The purpose of this study is to determine the comparison of student learning outcomes using picture media with audio-visual media in economics class X SMA Al-Washliyah 3 Medan. From the results of the study, the average learning outcomes using image media was 75.88 and the average learning outcomes using audio-visual media was 78.66. While the results of the calculation of the t test obtained significant results with = 0.05; df=18+18-2=34, then ttable = 2.032 and tcount=2,310, the results of this study found that tcount> ttable that is 2,310> 2,032, thus the hypothesis formulated in this study, namely: there is a comparison of student learning outcomes using image media with audio-visual media on economic subjects